FdC1 and Leaf-Type Ferredoxins Channel Electrons From Photosystem I to Different Downstream Electron Acceptors - Guan, Xiaoqian; Chen, Shuai; Voon, Chia Pao; Wong, Kam-Bo; Tikkanen, Mikko; Lim, Boon L. (Frontiers in Plant Science, 2018)
Plant-type ferredoxins in Arabidopsis transfer electrons from the photosystem I to multiple redox-driven enzymes involved in the assimilation of carbon, nitrogen, and sulfur. Leaf-type ferredoxins also modulate the switch between the linear and cyclic electron routes of the photosystems. Recently, two novel ferredoxin homologs with extra C-termini were identified in the Arabidopsis genome (AtFdC1, At4g14890; AtFdC2, At1g32550). FdC1 was considered as an alternative electron acceptor of PSI under extreme ferredoxin-deficient conditions. Here, we showed that FdC1 could interact with some, but not all, electron acceptors of leaf-type Fds, including the ferredoxin-thioredoxin reductase, sulfite reductase, and nitrite reductase. Photoreduction assay on cytochrome c and enzyme assays confirmed its capability to receive electrons from PSI and donate electrons to the Fd-dependent sulfite reductase and nitrite reductase but not to the ferredoxin-NADP+ oxidoreductase. Hence, FdC1 and leaf-type Fds may play differential roles by channeling electrons from photosystem I to different downstream electron acceptors in photosynthetic tissues. In addition, the median redox potential of FdC1 may allow it to receive electrons from FNR in non-photosynthetic plastids.